DRAINAGE NETWORK EVOLUTION OF THE PORTAIKOS RIVER (THESSALY) - Βρουχάκης Ι.; Βουβαλίδης Κ.; Σφέικος Α.; Μαργώνη Σ. (Bulletin of the Geological Society of Greece, 2018)
Portaikos river is a tributary of Pinios River located in Thessaly. It drains the southern part of Thessaly basin, and specifically the south part of the district of Tricala. This region is located at the border with the district of Karditsa. Portaikos River drainage basin covers an area of 294 km2, which is 2.8 % of the total drainage basin of Pinios River. The direction of Portaikos river drainage basin extends from SW-NE. The evolution of Portaikos River drainage network presents some specific morphometric features. Its analysis required the use of digital data, which were analyzed with G.I.S. software. During the study of the drainage network with the laws of drainage composition, we found a certain deviation of the 4t h and 5t h order streams. Geology has influenced significantly the estimated values of drainage density and frequency of the sub-basins. In some specific areas previous hydrographie features are inherited by the underlying rocks, which constitute the current surface morphology. The analysis of the rose diagrams of the tributaries showed a clear tendency in two main directions. The one extends from NE-SW and the other from NW-SE, almost vertical to each other. To conclude, the hypsometric (area altitude) analysis revealed that Portaikos River drainage network has developed upon a landmass of the western tectonic border of Thessaly basin.